Mantar Yönetim Ölçeği Geliştirilmesi Üzerine Bir Çalışma - Birincioğlu, Nihan; Tekin, Erol (Business and Economics Research Journal, 2018)
The aim of this study is to develop a mushroom management scale and to test its validity and reliability. The scale was applied to 216 research assistant for Exploratory Factor Analysis, and 240 different research assistant for Confirmatory Factor Analysis. As a result of the analysis, the Kaiser-Meyer-Olkin value is found 0,874 and the Scope Validity Index is found 0,95. The total variance ratio explained by the scale is 67,238%. In addition, according to the result of Explanatory Factor Analysis the scale consists of 4 factors and 19 items. These factors are described as "inadequate information sharing", " anxiety of power loss", "inadequate communication" and "lack of participatory management". Cronbach’s Alpha Internal Consistency Coefficient is calculated 0,90 and lastly, its test-retest correlation coefficient is calculated 0,82. At the same time it can be said that according to the Confirmatory Factor Analysis the scale has satisfactory coherence criteria. As a result, a valid and reliable Mushreoom Management Scale consisting of four sub-factors is developed.